2017
DOI: 10.1111/den.12910
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in endoscopic ultrasound‐guided biliary drainage

Abstract: Endoscopic ultrasound-guided biliary drainage (EUS-BD) is increasingly used as an alternative in patients with biliary obstruction who fail standard endoscopic retrograde cholangiopancreatography (ERCP). The two major endoscopic approach routes for EUS-BD are the transgastric intrahepatic and the transduodenal extrahepatic approaches. Biliary drainage can be achieved by three different methods, transluminal biliary stenting, transpapillary rendezvous technique, and antegrade biliary stenting. Choice of approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 78 publications
(184 reference statements)
0
80
0
Order By: Relevance
“…Endoscopic ultrasound‐BD is a treatment that has attracted significant attention; however, recent systematic analyses have shown that the high technical success rate of this procedure of 90–94.7% is associated with a high adverse event rate of 16.5–23.3% . As such, adverse events associated with EUS‐BD procedures remain important problems to be resolved.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic ultrasound‐BD is a treatment that has attracted significant attention; however, recent systematic analyses have shown that the high technical success rate of this procedure of 90–94.7% is associated with a high adverse event rate of 16.5–23.3% . As such, adverse events associated with EUS‐BD procedures remain important problems to be resolved.…”
Section: Discussionmentioning
confidence: 99%
“…Since its first report in 2001, endoscopic ultrasound‐guided biliary drainage (EUS‐BD) has emerged as a new biliary decompression procedure and has been increasingly used as an effective alternative for biliary obstruction patients with failed ERCP . In the last decade, EUS‐BD has been attracting considerable attention and various endoscopic techniques have been described for its implementation . Among these, EUS‐BD with transmural stenting can be carried out by two main access routes: choledochoduodenostomy (CDS) and hepaticogastrostomy (HGS).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, much attention has been paid to a novel indwelling drainage technique under endoscopic ultrasound (EUS) guidance . EUS‐guided gallbladder drainage (EUS‐GBD) has been proposed as an alternative to PTGBD in patients with cholecystitis who cannot undergo cholecystectomy.…”
Section: Introductionmentioning
confidence: 99%